Sesamoids in anurans: New data, old issues - Ponssa, María Laura (2010)
Sesamoids are skeletal elements rarely considered in studies of the vertebrate skeleton. In this work, we integrate ontogenetic data of anuran sesamoids in two species (Leptodactylus latinasus and Pleurodema cf. guayapae), the related structures (tendons, muscles, and joints) in L. latinasus, and a survey of sesamoid distribution in 185 anuran taxa. Our main goals are: (1) to contribute to the knowledge of the comparative anatomy of sesamoids in tetrapods; (2) to provide additional developmental evidence to interpret the ontogenetic pattern of sesamoids in anurans, as a key to elucidate that of tetrapods in general; (3) to provide data about tendon development in relation to sesamoid development in anurans for the first time; and (4) to propose a pattern of anuran sesamoid distribution. The homologies of sesamoids across tetrapods are discussed here. Observations were made in cleared and stained skeletal whole-mounts. Fifty-four sesamoids were found in anurans, thirty-seven of which occur in L. latinasus. The traditional point of view of embedded sesamoids always resulting from biomechanical stimuli of a previously existing tendon is not sustained by our data. Many sesamoids arise before the differentiation of a tendinous tissue. Our survey results in a data set where the two big anuran clades, Hyloides (12 families) and Ranoides (14 families), were represented. The matrix has 38% missing entries. Most of the surveyed sesamoids have multiple origins, with only three of them (about 19%) having one origin.